Perencanaan Sistem Penyediaan Air Minum (SPAM) di Desa Komba Komba Kecamatan Kabangka Kabupaten Muna - Riamin, La; Ilham, Ilham; Assiddieq, Moch. (Universitas Muhammadiyah Kendari, 2022)
Komba-Komba village is one of the coastal villages in Kabangka District, Muna Regency. Based on BMKG rainfall data in Bau-Bau City in 2015, the water source used in the village experienced a drought due to the dry season which was different from the previous year. One alternative to meet the needs of the community is to utilize the Fotuno Sangia River which is ± 4.7 km from the coast as a source of clean water. The Fotuno Sangia River has a discharge of 2000 L/s with water quality not exceeding the clean water quality standards. In Komba-Kamba Village, a Drinking Water Supply System (DWSS) will be planned as an effort to meet the community's water needs until 2031 by utilizing the Fotuno Sangia River as a water source. The total population is calculated using the geometric method so as to produce a projected population of 1397 people in 2031, with 70% of the clean water needs served, which is 88.99 m3/day. the intake useful capacity volume is planned to be 1.5 m3. The volume of water entering the intake is 36 L/s. The pump used has a capacity of 4.12 L/s with a duration of 6 hours to produce a pump of 88.99 m3. The pipe used for water distribution is a 4-inch diameter PVC pipe, with a water velocity in the pipe of 0.51 m/s. The volume of the useful capacity of the reservoir building is planned at 72 m3 based on fluctuations in water use/hour.